IMPLEMENTASI JAMINAN MUTU ISO/IEC 17025: 2017 DI BALAI BESAR LITBANG PASCAPANEN PERTANIAN BOGOR - Diyono, Wahyu; Helmi Haris, (Jurnal Ilmiah Pangan Halal, 2021)
The BB-Postharvest testing laboratory has competence for chemical, biochemical, physical analysis, quality testing and food safety. Some of them have received recognition from the national accreditation agency KAN in accordance with the ISO/IEC 17025:2017 quality system and the SNI ISO/IEC 17043:2010 quality system. The research aim was to get proficiency tests, comparative tests, recovery, and sample control. The results of the pesticide residue proficiency test followed by the postharvest laboratory for diazinon and chlorphyrifos ethyl were -0.6225 and 0.4491. The calculated T after being compared with three other labs had the same value, namely 6.31 while the T table was 12.71. The total fat of powdered milk was significantly different from that of Vicmalab and the protein content of both powdered milk and biscuits was significantly different from that of Vicmalab. The value of chlorphyrifos ethyl pesticide residue recovery test was 115.59% while the acceptability was 80-120%. For the control chart, a graph has been made to be applied to each test. The quality assurance of testing in the Chemistry laboratory, Postharvest BB meets the acceptance requirements.